A thermodynamical approach to the formation reactions of sodium-doped Cu(In,Ga)Se-2 - Hock, Rainer; et al. (ELSEVIER SCIENCE SA, 2006)
This work describes the influence of sodium doping on the formation reactions of the semiconductor material Cu(In,Ga)Se-2. Assuming the sodium dopant to act as a surface catalyst by formation of sodium polyselenides, we estimate the shift in the reaction enthalpies for the formation of binary selenides. Since the release of selenium from sodium polyselenides is an endothermic process, five of six possible reactions resulting in copper selenides are energetically suppressed whereas all indium and gallium selenides can still be formed exothermically. Furthermore, we have applied the effective heat of formation model on the ternary Cu-In-Se system to predict the first compound being formed during the selenisation of the metallic precursor. Our model predicts that sodium doping does not influence which selenide compound will be formed at first, but that influences consecutive reactions by shifting their reaction enthalpies. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: chalcogenides; thin films; crystal growth; X-ray diffraction; thermodynamic properties